SISTEM INFORMASI PELAYANAN KESEHATAN RAWAT INAP MENGGUNAKAN FRAMEWORK LARAVEL - Tristiyanto Tristiyanto; Adelliani Adelliani (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The health services is a place that provides health services which include inpatient, outpatient and emergency services. Inpatient is a service provided to patients, where the patient has to undergo a treatment process which is handled directly by a doctor in accordance with the complaint of the disease. Easy service and fast handling from the health care unit both in terms of rooms and from the patient side are of course very much needed by inpatients. The problem that occurs is that it is difficult for inpatients to know the availability of rooms, making it difficult for patients to undergo treatment. Apart from the availability of rooms, the inpatient registration system is still being used in paper format. This results in piles of patient files making it difficult to find patient data and causes errors to be encountered when making reports due to loss of patient files. In this research, an Inpatient Information System will be built that can be used by various health services so that all inpatient data in health services can be integrated into this system. The research method used in this research uses the waterfall method, which starts from the specification of user requirements, planning, modeling, construction and software implementation. This system is built using the Laravel Framework using the PHP language which is used to build web-based applications in a more structured way. This information system was built with the aim of helping and facilitating the services provided to patients in the health care unit. Both in terms of inpatient registration, making patient reports, managing patient data and the availability of inpatient rooms.